Control of the transmission length in the prestressed hollow-core slabs using values of the strand end slip - Tur, Victor; Fic, Stanisław (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
It is shown [1] that even though the production of precast pre-tensioned concrete elements started more than 50 years ago, no one has ever succeeded in determining the real transmission length or in obtaining adequate measures to control it, due to the quality of the production. These arrears are confirmed by the study of existing standards. In general, it is assumed that the measurement of the magnitude of the slippage of strand at the end of hollow core prestressed slab is an indirect method of estimation and control of the value of the transmission length. One should mention that EN1168 and EN13369 that regulate requirements of designing and production of hollow-core slabs are applied as the method of control. Based on a particular bond-slip relation for strands, a non-linear equation is developed for the transmission length and for the slippage of prestressed strand, taking into account such factors as the concrete strength at transfer, the degree of the initial prestress type and diameter of tendons. These equations have been used for the control of transmission length of the strands calculated by different methods available recently, including a code provision. Then they were compared to measured data, obtained in production control of the hollow-core slabs.